Ювілей факультету будівництва НТУ «Дніпровська політехніка» - Солодянкін, О. В.; Скобенко, О. В.; Солодянкіна, О. А. (Журфонд, 2021)
Стаття присвячена історії створення та розвитку факультету будівництва Національного технічного університету «Дніпровська політехніка», всім сферам його діяльності – освітній, науково-дослідній, кадровій. В першу чергу наведені факти і досягнення кафедр факультету в підготовці і випуску гірничих інженерів – шахтобудівельників та маркшейдерів з дня заснування шахтобудівельного факультету в Дніпропетровському гірничому інституті дотепер. Більш детально розглянуті перші роки становлення факультету, його структуру, створення організаційно-методичних основ підготовки кваліфікованих фахівців. Наведені напрями наукової діяльності під керівництвом провідних вчених факультету, лідерів наукових шкіл, приклади найбільш ефективних технологічних розробок і значних наукових досягнень. У статті наведені дані про деканів факультету з дня його заснування, відомості про видатних вчених і випускників факультету. Сьогодення та перспективи подальшого розвитку кафедр факультету розглянуті в призмі збереження традицій в підготовці фахівців і з урахуванням сучасних викликів вітчизняних і світових проблем. Дана структура факультету на сьогодні, перелік напрямів та освітніх програм підготовки фахівців. Наведені найважливіші результати та досягнення колективу факультету останніх років та плани на найближчу перспективу.

The article is devoted to the history of the creation and development of the Faculty of Construction of the NTU Dnipro Polytechnic all areas of its activities – educational, research, personnel. First of all, the facts and achievements of the departments of the faculty in the education and graduation of mining engineers – mine builders and mine surveyors from the day of the foundation of the Faculty of Mine Construction at the Dnepropetrovsk Mining Institute to the present are given. The first years of the formation of the faculty, its structure, the creation of organizational and methodological foundations for the education of qualified specialists are considered in more detail. The directions of scientific activity under the guidance of leading scientists of the faculty, leaders of scientific schools, examples of the most effective technological developments and significant scientific achievements are shown. The article provides data on the deans of the faculty from the day of its foundation, information on outstanding scientists and graduates of the faculty. The present and the prospects for further development of the departments of the faculty are considered in the prism of preserving traditions in the training of specialists and taking into account the modern challenges of domestic and world problems. The structure of the faculty is given today, a list of directions and educational programs for training specialists. Cited the most important results and achievements of the faculty staff in recent years and plans for the near future.
Anniversary of the Faculty of Construction Dnipro University of Technology
Keywords: шахтобудівельний факультет; факультет будівництва; історія; Дніпропетровський гірничий інститут; Дніпровська політехніка; Faculty of Mine Construction; Faculty of Construction; history; Dnipropetrovsk Mining Institute; Dnipro Polytechnic